Estimation of Serum YKL‐40 by Real‐Time Surface Plasmon Resonance Technology in North‐Indian Asthma Patients. Issue 2 (12th September 2016) - Naglot, Sarla; Aggarwal, Praveen; Dey, Sharmistha; Dalal, Krishna
Abstract : Background: Many studies reported for estimating serum YKL‐40 using ELISA or RIA methods. This study introduces the plausible utilization of real‐time surface plasmon resonance (SPR) technology in investigating the expression of serum YKL‐40 protein levels and ELISA method for serum IgE in bronchial asthma. Methods: A commercially available BIAcore 2000 instrument, based on SPR technology, was utilized for assessing serum YKL‐40 levels in a control sample size of 45 and active sample size of 97. Antibody immobilization was optimized to obtain the best sensor performance and a sensitive analytic detection. A commercially available ELISA kit was utilized for detecting serum IgE to estimate allergic condition‐associated asthma. Results: The results of SPR technology could distinctly classify with highly statistical significance, the asthma severities by estimating the elevated levels of YKL‐40 in blood sera of minute quantities (up to 0.33 ng/ml), and thus differentiates superior utility in comparison with ELISA method. No statistically significant correlation of YKL‐40 and IgE was observed. Conclusions: Serum YKL‐40 may be used as a protein marker in classifying asthma severity by applying SPR technology as a reliable, label‐free, highly sensitive, and cost‐effective tool.